Multiparticle Production in QCD Jets - Andersen, JR; Brook, N; Dokshitzer, Y; Khoze, V; Kittel, W; Ochs, W; Stirling, W; Zanderighi, G (2002)
We briefly summarise the main results presented at the IPPP Workshop on Multiparticle Production in QCD Jets, held in Durham in December 2001.